The Tale of Nicolai and the Law of Return - Ofek, David (Eden Productions, 2008)
Verzio FF Submission The story of Nicolai begins in a tiny, remote village in the Romanian region of Moldavia. With the collapse of communism, Nicolai - like many thousands of other villagers - suddenly found himself out of work, so he decided to seek his fortune overseas, far from his family and home. For three years he worked as a guest laborer in Israel, exploited to the hilt by the company that sent him there. He had little contact with his wife, who gave birth in his absence. Finally, determined to take control of his destiny, Nicolai fled his employer and became an "illegal". He was caught by the police and sent to prison, but suddenly his life took an abrupt turn and at once everything changed. Nicolai plays himself in this film, and relives the dramatic events of his life.